Latihan Tarik Nafas dalam dan Relaksasi Otot Progresif dalam Manajemen Stress pada Remaja di SMA IT Baitul Jannah - Eka Yudha Chrisanto; Khoirul Nadira; Siti Helina Mariyam; Riswan Hadi; Monica Bela Dwi Sintia; Muhammad Irgi; Ika Saraswati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Stress and depression problems can have many negative impacts on teenagers, including mental health problems in teenagers, and can even lead to dangerous behavior. In Indonesia, the prevalence of stress in the younger generation is increasing from year to year, reaching 6.0% of the population. Maybe 6% still feels small. However, this number continues to increase every year as more and more young people participate in bullying, and bullying has become more common these days. The ability to maintain self-control in the face of overwhelming situations, people, and events is also the definition of stress management. If managed well, stress transforms from an obstacle to a motivator of social, intellectual, and psychological well-being. The aim of this activity is to increase knowledge in teenagers about stress management. It is hoped that students will be able to understand and implement stress management by means of deep breathing exercises and progressive muscle relaxation. The results of the questionnaire obtained from these four categories were 910 points. Apart from that, the findings from this activity were that 46 respondents (100%) could do deep breathing and progressive muscle relaxation exercises very well. It is important for students to know how to deal with stress, especially since the source of stress comes from the academic process